PENERAPAN STRATEGI PREVIEW, QUESTION, READ, REFLECT, RECITE, REVIEW (PQ4R) TERHADAP PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS XI IPA SMAN 1 SINGKARAK KABUPATEN SOLOK - Yucarini, Sauci; Zulfaneti, Zulfaneti; Yuliana Fitri, Dewi (STKIP PGRI Sumbar, 2014)
ABSTRAKÂ This research is motivated by the students understanding on mathematics concept are still low and the students quickly forgotten in considering the material they have learned. This research was aimed to determine whether students understanding on mathematics concept by implementing PQ4R strategies better than students understanding on mathematics concept by applying conventional learning in class XI Science SMAN 1 Singkarak. This research is an experimental study with randomized research design of the subject. Data analysis techniques are used the hypothesis is t-test. Hypothesis test results obtained t = 5.27 and t table = 1.678 at Î± = 0.05, so the hypothesis is accepted. So it can be concluded that the students understanding on mathematics concept by applying PQ4R strategies is better than the studentsâ understanding on mathematical concepts by applying conventional learning in class XI Science SMAN 1 Singkarak.